2018
DOI: 10.1016/j.seizure.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of levetiracetam for reducing rolandic discharges in comparison with carbamazepine and valproate sodium in rolandic epilepsy

Abstract: A R T I C L E I N F O Keywords:Levetiracetam (LEV) Rolandic epilepsy (RE) Electroencephalogram (EEG) Rolandic discharge (RD) Anti-epileptic drug (AED) A B S T R A C T Purpose:The main purpose of this study was to compare the efficacy of levetiracetam (LEV) with the older antiepileptic drugs (AEDs) for preventing atypical evolution in children with Rolandic epilepsy (RE). Accordingly, the present study compared the efficacy of older AEDs (carbamazepine (CBZ) and valproate sodium (VPA)) with LEV in reducing rola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Two studies performed by Wang et al and Sun et al applied the Wechsler Intelligence Scale to explore the effect of ASMs and revealed that VPA was associated with a worse effect on cognitive improvement than OXC and LEV (Sun, 2015;Wang WX et al, 2019). Similar discrepant results of other ASMs can also be seen in different comparative studies (Kanemura et al, 2018;Kim et al, 2018;Tacke et al, 2018).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Two studies performed by Wang et al and Sun et al applied the Wechsler Intelligence Scale to explore the effect of ASMs and revealed that VPA was associated with a worse effect on cognitive improvement than OXC and LEV (Sun, 2015;Wang WX et al, 2019). Similar discrepant results of other ASMs can also be seen in different comparative studies (Kanemura et al, 2018;Kim et al, 2018;Tacke et al, 2018).…”
Section: Introductionsupporting
confidence: 83%
“…For example, Tacke et al conducted an RCT study ( Tacke, et al, 2018 ) to examine the influence of ASM treatment (STM and LEV) on EEG and revealed that treatment with both STM and LEV significantly reduced the spike-wave index, with no differences between the two treatment groups. A study ( Kanemura, et al, 2018 ) conducted by Kanemura et al reported similar results and revealed that LEV seems superior to CBZ and VPA in its ability to suppress rolandic discharges (RDs) interictally in children with BECTS. Our meta-analysis results showed that STM was related to a higher probability of EEG normalization than placebo, while there was no difference between VPA versus CBZ, OXC, and LEV versus CBZ.…”
Section: Discussionmentioning
confidence: 75%
“…In this study, levetiracetam plus sodium valproate showed statistically significant association with reduction of SWI. In comparison with carbamazepine and sodium valproate, levetiracetam was superior in suppressing rolandic discharges, however, the effects of those three drugs in controlling seizures were the same according to one study (29). A randomized controlled trial revealed that both levetiracetam and sulthiame have beneficial effects on EEG normalization (23).…”
Section: Discussionmentioning
confidence: 99%
“…currently reported that levetiracetam was effective and well tolerated as monotherapy in pediatric patients with rolandic epilepsy, and it seemed to be superior to carbamazepine and valproic acid in its ability to suppress rolandic discharges in children; however, the trends of the efficacy of levetiracetam were not significantly higher. [ 15 16 17 ] Asadi-Pooya et al . reviewed the current literature and suggested that levetiracetam is probably a better choice compared with carbamazepine to be prescribed for children with rolandic epilepsy due to its better effect on cognitive problems, better tolerance, and fewer side effects in comparison with other antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 99%